Arabic Language Learning from the Students' Perspective: A Descriptive Study on Responses, Motivation, and Learning Challenges in Madrasah: Pembelajaran Bahasa Arab dari Perspektif Siswa: Studi Deskriptif tentang Respons, Motivasi, dan Tantangan Belajar di Madrasah - Uno, Selfiyanti; Hairuddin (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Arabic language learning in madrasah often encounters challenges due to the complexity of the language and the suboptimal teaching methods applied. Purpose: This study aims to explore the perspectives, motivations, and challenges experienced by ninth-grade students at MTs Negeri 1 Boalemo in learning Arabic, as well as to examine the effectiveness of instructional strategies used by teachers. Method: Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation. Results and Discussion: Findings reveal that although students are highly motivated—primarily for religious reasons—the predominance of conventional methods hinders their communicative competence. Additionally, learning media used in class do not sufficiently support the diverse learning styles of students.. Conclusions and Implications: This study emphasizes the importance of communicative and contextual approaches to bridge students’ motivation with optimal learning outcomes.